Economical and efficient technique for a static localized maximum sun lux determination - Ahmed H. Ali; Adel S. Nada; Ahmed S. Shalaby (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Solar energy is one of the most promising renewable sources that is currently being used worldwide to contribute for meeting rising demands. In this paper solar irradiance measurement will experimentally carried out in two different regions in Egypt; Cairo and Luxor cities. This paper proposes a simple solar lux measurement using a light dependent resistor (LDR) with an arduino kit. This technique is based on two approaches which are coarse and fine maximum sun lux determination. This is based on the predetermined 260 vertical slop of the LDR. Coarse tuning determines one of the reach sun lux quarter (900) of horizontal quad. The fine tuning allocates the optimized 100 in which; the maximum sun lux can be obtained. The optimal values of sun lux were found between the (90o–180o) quarter. This study confirms that the narrow ten degrees (95o-105o) are the optimized static sun lux extraction for the two site field measurements. This novel technique can be used for locating the angle of best installations for the solar cell at which maximum solar energy can be extracted.